Authenticity, trust, affect, and loyalty in Indonesia’s specialty coffee market: Evidence from Upala coffee & eatery - Syamofi, Sutas (Privietlab, 2024)
This study investigates how brand authenticity and brand trust shape downstream brand affect and brand loyalty in a single-brand context—Upala Coffee & Eatery in East Jakarta. Using a descriptive–associative, quantitative, cross-sectional survey with purposive sampling (n ≈ 100), we measured three authenticity facets—quality commitment, heritage, and sincerity—and two trust facets—brand reliability and brand intention—alongside brand affect and brand loyalty. Measurement diagnostics (PLS-SEM, SmartPLS 4) indicate satisfactory reliability and convergent/discriminant validity (CR > 0.80; AVE > 0.50). Structurally, authenticity explains meaningful variance in trust; sincerity and quality commitment significantly raise both trust dimensions, while heritage is not a significant driver. On the outcome side, brand intention (benevolence) strongly increases brand affect and modestly increases loyalty, whereas brand reliability behaves like a hygiene factor and does not significantly lift affect or loyalty. Brand affect exerts the strongest immediate influence on loyalty. Overall, the findings show that “lived” authenticity—consistently enacted values and quality follow-through—builds benevolent trust, which, in turn, generates positive affect and repeat-patronage intentions. For emerging coffee brands, prioritizing sincerity-in-action, transparent service recovery, and tangible quality cues is likely to yield greater loyalty than relying on heritage narratives alone.